Аналіз факторів формування пропозиції плодової продукції на ринку - Болтянська, Лариса Олексіївна; Болтянская, Лариса Алексеевна; Boltianska, Larysa (My University, 2016)
UK: Сучасний ринок функціонує під впливом попиту та пропозиції. Суб’єктами ринку, що формують ці елементи, виступають споживачі (регулюють попит) та сільськогосподарські підприємства різних форм власності та особисті господарства населення (утворюють пропозицію.) Товарна пропозиція продукції галузі садівництва змінюється під впливом різноманітних факторів. У статі проаналізовано чинники, які напряму формують пропозицію плодової продукції на вітчизняному ринку. EN: Modern market is functioning under the influence of macroeconomic elements: supply and demand. Demand for agricultural product market is made by consumers: processors population. Subjects that form the offer in the market are the agricultural enterprises of all forms of ownership and individual households. However, the main factors forming supply of fruits are the factors that influence the growth of production and accordingly the volume of sales of agricultural enterprises and farms. It should also be noted fact feasibility of production of certain products for producers: grow what is profitable, so it is necessary to fill the agricultural products market. Soft and fruit products offer in the domestic market formed by agricultural enterprises and farms. The main producers of the current moment are the households, which concentrates the largest share of the fruit-bearing area of perennial plants, the highest level of performance under trees and weighty fate of commodity production of its market. However, in terms of market primary purpose of commodity production is the profit from the sale, serving the main purpose of production in the fruit farms as opposed to households that use products even for their own needs. Therefore, specialized enterprises should achieve highly efficient on the field through improved use of existing, implementation of resource intensive technologies soft and fruit growing crops, expanding the network of companies specialized in the production of fruits and berries, placing gardens improvement, improve the structure of rock and varietal plantings.
Analysis of factors of proposal fruit products on the market
Keywords: аграрний ринок; товарна пропозиція; фактори формування пропозиції; розміщення; ефективність виробництва; продуктивність плодів; agricultural market; commodity supply; factors of supply; location; efficiency; productivity of fruits